Study on antibiotics activity in vitro and treatment effects in place in the experimental burns of EB product isolated from the rhizome of Eleutherine bulbosa - Hong Van, Nguyen Thi; Nguyet Que, Do Thi; Hang, Nguyen Thu; Loan, Le Thi; Anh, Luu Tuan; Hoan, Nguyen Van (Academia Journal of Biology, 2014)
The products EB containing of eleutherine and isoeleutherine have been extracted from the rhizome of Eleutherine bulbosa and showed the antibacterial effect on experimental animals. Based on the results of diameter of sterile ring using the agar diffusion method, EB products have a significant antibacterial effect against Bacillus subtilis, Staphylococcus aureus, Shigella flexneri DT 112, Proteus mirabilis BV 108 and Bacillus pumilus at concentrations of 50 μg/ml and 100 μg/ml. The EB products exhibited also their antibacterial activity in vivo on the experimental thermal burn in the rabbit skin, reducing the density of bacterial/cm2 at 7 days after treatment by EB ointment, these antibacterial effect of EB is equivalent to sulfadiazine - 1% silver.